Distinct Leishmania species infecting wild caviomorph rodents (Rodentia: Hystricognathi) from Brazil. - Renata Cássia-Pires; Mariana C Boité; Paulo S D'Andrea; Heitor M Herrera; Elisa Cupolillo; Ana Maria Jansen; André Luiz R Roque (Public Library of Science (PLoS), 2014)
Caviomorph rodents, some of the oldest Leishmania spp. hosts, are widely dispersed in Brazil. Despite both experimental and field studies having suggested that these rodents are potential reservoirs of Leishmania parasites, not more than 88 specimens were analyzed in the few studies of natural infection. Our hypothesis was that caviomorph rodents are inserted in the transmission cycles of Leishmania in different regions, more so than is currently recognized.We investigated the Leishmania infection in spleen fragments of 373 caviomorph rodents from 20 different species collected in five Brazilian biomes in a period of 13 years. PCR reactions targeting kDNA of Leishmania sp. were used to diagnose infection, while Leishmania species identification was performed by DNA sequencing of the amplified products obtained in the HSP70 (234) targeting. Serology by IFAT was performed on the available serum of these rodents.In 13 caviomorph rodents, DNA sequencing analyses allowed the identification of 4 species of the subgenus L. (Viannia): L. shawi, L. guyanensis, L. naiffi, and L. braziliensis; and 1 species of the subgenus L. (Leishmania): L. infantum. These include the description of parasite species in areas not previously included in their known distribution: L. shawi in Thrichomys inermis from Northeastern Brazil and L. naiffi in T. fosteri from Western Brazil. From the four other positive rodents, two were positive for HSP70 (234) targeting but did not generate sequences that enabled the species identification, and another two were positive only in kDNA targeting.The infection rate demonstrated by the serology (51.3%) points out that the natural Leishmania infection in caviomorph rodents is much higher than that observed in the molecular diagnosis (4.6%), highlighting that, in terms of the host species responsible for maintaining Leishmania species in the wild, our current knowledge represents only the "tip of the iceberg."